O ensino de matemática através da compreensão da linguagem matemática - Dias, Claudeir (2019)
This dissertation presents a teaching proposal aimed at teaching mathematics through the understanding of mathematical language. This proposal is based on the methodology that must solve the exercise in several types of abstractions, moving from the formal analytical description in natural language to the synthetic description in mathematical language and show that mathematical synthetic language is a model applicable in several situations. To facilitate the understanding of the proposal, we present the problematization that led us to this research, making a historical survey on the teaching of mathematics, especially the use of exercises as a teaching strategy. To facilitate the visualization of the methodology of the proposal, we gave examples of how it would be the application in the room of the methodology and a report of experience on two observations, the first with people who have finished high school and the second with high school students. Finally, in the final considerations we present the results achieved.